Relevance of Emotional Intelligence and Work Performance among Managers in the Hotels of Malaysia - Wang, Wei (2012)
This paper describe the research on the relationship between Emotional Intelligence (EI) and work performance among managers in hotels of Malaysia. Beside their experiences, knowledge and skills, emotion plays an important role in pushing individual to produce and perform the best. Emotion is critical in motivating, persuading, communicating, leading and controlling individuals and groups. Until research used the quantitative method Questionnaires were distributed among managers using simple random sampling. The questionnaire has been designed to assess how effectively individual deal with emotion and how their work performance is. The findings of this empirical study would highlight the importance of EI in hotels and give details on EI factors which influence the work performance of employees. Besides, the mixture tests which involved one way ANOVA, correlations and regressions analysis were used to test the objectives and hypothesis by SPSS. The findings indicate that EI is positively related to work performance. And one of the findings also implies that working experience can be a potential predictor of high level of Emotional Intelligence. It explains why organizations nowadays prefer to hire people with working experience.